Comparison of Primary Human Fibroblasts and Keratinocytes with Immortalized Cell Lines Regarding their Sensitivity to Sodium Dodecyl Sulfate in a Neutral Red Uptake Cytotoxicity Assay - Ölschläger, Veronika; Schrader, Andreas; Hockertz, Stefan (Arzneimittelforschung, 2009)
Cell lines present a valuable tool for in vitro assessment of skin damage caused by application of cosmeticals or pharmaceuticals. They form a reproducible test system under controllable test conditions and, in many cases, can be used as alternatives to animal testing in order to assess the compatibility of drugs or cosmetics and human skin. Yet, it can not necessarily be assumed that the behavior of cultured cells, when treated with different substances, is exactly consistent with the behavior of cells being part of a live organism. Becoming immortal, cells exhibit changes in genotype and/or phe-notype, possibly resulting in modified reactions to external influences. Therefore, to obtain results close to in vivo studies, it seems apparent to use primary cells for testing that have not yet undergone any modifications. To compare the properties of primary fibroblasts (Normal Human Dermal Fibroblasts, NHDF) and primary keratinocytes (Normal Human EpidermalKeratinocytes, NHEK) with those of immortal cell lines (3T3 (ACC 173) Swiss albino mouse fibroblasts and HaCaT (human, adult, low calcium, high temperature, human adult skin keratinocytes) cells), their sensitivities in cytotoxicity assays have been assessed. While both fibroblast cell cultures showed similar sensitivities towards sodium dodecyl sulfate (SDS), primary keratinocytes died at SDS concentrations about three times lower than the immortal HaCaT cells.
Keywords: Cytotoxicity assays; Immortalized cell lines; Primary human fibroblasts; Primary human keratinocytes; Sodium dodecyl sulfate